2001
DOI: 10.1038/35053509
|View full text |Cite
|
Sign up to set email alerts
|

The molecular dynamics of pain control

Abstract: Pain is necessary for survival, but persistent pain can result in anxiety, depression and a reduction in the quality of life. The discriminative and affective qualities of pain are both thought to be regulated in an activity-dependent fashion. Recent studies have identified cells and molecules that regulate pain sensitivity and the parallel pathways that distribute nociceptive information to limbic or sensory areas of the forebrain. Here, we emphasize the cellular and neurobiological consequences of pain, espe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
345
0
12

Year Published

2004
2004
2010
2010

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 525 publications
(369 citation statements)
references
References 95 publications
12
345
0
12
Order By: Relevance
“…Even more striking is that a large percentage of these neurons do not fit into a traditional neurochemical pheno- type. For example, if one considers the classical markers of peptidergic and nonpeptidergic neurons (Hunt and Mantyh, 2001), one-third of TRPM8 TG neurons are immunoreactive for CGRP (even fewer in DRG), whereas none bind IB4. However, based on these criteria, over two-thirds of TRPM8 TG neurons fall outside of this classification (i.e., those that are CGRP and IB4 negative).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Even more striking is that a large percentage of these neurons do not fit into a traditional neurochemical pheno- type. For example, if one considers the classical markers of peptidergic and nonpeptidergic neurons (Hunt and Mantyh, 2001), one-third of TRPM8 TG neurons are immunoreactive for CGRP (even fewer in DRG), whereas none bind IB4. However, based on these criteria, over two-thirds of TRPM8 TG neurons fall outside of this classification (i.e., those that are CGRP and IB4 negative).…”
Section: Discussionmentioning
confidence: 99%
“…Peptidergic fibers, labeled by CGRP immunoreactivity, project to lamina I and the outer regions of lamina II (IIo) (McNeill et al, 1988;Zylka et al, 2005). In contrast, nonpeptidergic neurons labeled by IB4-binding project primarily to the inner region of lamina II (IIi), whereas lamina IIi and III can be visualized by labeling of interneurons expressing the ␥-isoform of protein kinase C (PKC␥) (Silverman and Kruger, 1988;Hunt and Mantyh, 2001;Zylka et al, 2005). In spinal cords of Trpm8 GFP mice, there was almost complete overlap of GFP-and CGRPlabeled fibers (Fig.…”
Section: Central Projections Of Trpm8 Fibers In the Dorsal Spinal Cordmentioning
confidence: 99%
See 1 more Smart Citation
“…The sensory component of pain is defined as nociception and is required for survival and the maintenance of the integrity of the organism. However, sustained or chronic pain, particularly in humans, can result in secondary symptoms such as anxiety, depression, and a marked decrease in the quality of life (1,2). Specific cell types and several molecules have been identified that detect and regulate nociceptive activity.…”
mentioning
confidence: 99%
“…This tachykinin has been suggested to be involved in numerous functions, including transmission of noxious stimuli to the spinal cord (Hunt and Mantyh, 2001). The SP is released by dorsal root ganglion (DRG) afferents and can act on neurons of the dorsal horns, a laminar structure that receives somatosensory inputs.…”
Section: Introductionmentioning
confidence: 99%